Interface engineering breaks both stability and activity limits of RuO2 for sustainable water oxidation - Kun Du; Lifu Zhang; Jieqiong Shan; Jiaxin Guo; Jing Mao; Chueh-Cheng Yang; Chia-Hsin Wang; Zhenpeng Hu; Tao Ling (Nature Communications, 2022)
RuO2 encounters critical electrochemical dissolution issues during oxygen evolution reaction and it remains a grand challenge to achieve stable and active RuO2 electrocatalyst. Here, the authors report breaking stability and activity limits of RuO2 by constructing a RuO2/CoO x interface.